VALUE OF RHEUMATIC PATIENTS' AWARENESS OF HAVING INFECTIOUS COMORBIDITIES - Rimma Mikhailovna Balabanova; V N Sorotskaya; I B Vinogradova; G G Koreshkov (Современная ревматология, 2010)
Subjects and methods. Four hundred and ninety-five patients with various RDs were interviewed by a questionnaire. A comparison group comprised 250 patients with non-RDs and 150 physicians. Results. The patients with RD frequently reported to have nasopharyngeal infection. The latter was accompanied by an exacerbation of articular syndrome in more than half of the patients with RD. The rate of pneumonias experienced by patients with systemic lupus erythematosus (SLE) (10/55) engages our attention. Urogenital tract infections (mainly cystitis and pyelonephritis) are more typical of patients with rheumatic arthritis (RA) and those with osteoarthrosis (OA), respectively. The clinical manifestations of herpes simplex virus type 1 (HSV-1) recurred most frequently in patients with SLE and those with OA and less in patients with RA. The percentage of HSV-1 recurrences was high in the medical staff. Conclusion. The findings suggest that it is necessary to thoroughly collect medical history data especially in patients who need aggressive immunosuppressive therapy as activation of latent infection makes management of these patients difficult